The reaction of Cp*Ir(CO)(CI)(p-C6F4CN) with nucleophiles. - Quek, Sylvia Shu Wei. (2010)
The reactions of Cp*Ir(CO)(Cl)(p-C6F4CN) with nucleophiles such as NaOMe and NaH were conducted. The reactions probably proceeded via a salt elimination of NaCl or a base hydrolysis of the nitrile functional group.